2021
DOI: 10.1210/clinem/dgab060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Definition of Pseudohypoparathyroidism Variants

Abstract: Pseudohypoparathyroidism (PHP) and pseudopseudohypoparathyroidism (PPHP) are caused by mutations and/or epigenetic changes at the complex GNAS locus on chromosome 20q13.3 that undergoes parent-specific methylation changes at several differentially methylated regions (DMRs). GNAS encodes the alpha-subunit of the stimulatory G protein (Gsα) and several splice variants thereof. PHP type Ia (PHP1A) is caused by heterozygous inactivating mutations involving the maternal exons 1-13. Heterozygosity of these maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 115 publications
(111 reference statements)
4
64
0
Order By: Relevance
“…1 B , C , Table 1 ). On the PTH1R‐R186H mutant, the maximum response to PTH( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) was moderately higher than that observed on PTH1R‐WT (Emax = 118% ± 4%, p = 0.002, Table 1 ), whereas the potency of the response tended to be slightly (approximately threefold) weaker than that of the ligand on PTH1R‐WT. The reason for the increase in Emax is not clear, because the patient phenotype predicts a deficiency in responsiveness to PTH, which is at least suggested by the trend toward reduced potency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 B , C , Table 1 ). On the PTH1R‐R186H mutant, the maximum response to PTH( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) was moderately higher than that observed on PTH1R‐WT (Emax = 118% ± 4%, p = 0.002, Table 1 ), whereas the potency of the response tended to be slightly (approximately threefold) weaker than that of the ligand on PTH1R‐WT. The reason for the increase in Emax is not clear, because the patient phenotype predicts a deficiency in responsiveness to PTH, which is at least suggested by the trend toward reduced potency.…”
Section: Resultsmentioning
confidence: 99%
“…5 C , Table 2 ). The relative responses induced by PTH(1‐28) and PTHrP( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ) on PTH1R‐R186H therefore differed from those obtained on this mutant receptor with the intact peptides, as the Emax of the response to PTH(1‐34) was increased by ~18% and potency tended to be approximately threefold weaker, whereas the response to PTHrP(1‐36) was unchanged for efficacy and approximately twofold stronger in potency. These differences suggest that residues in the 29–34 and 29–36 regions of PTH(1‐34) and PTHrP(1‐36), respectively, can modulate the impact that the R186H mutation located in TM1 of the receptor has on the overall ligand interaction process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(22‐ 24 ) A 3‐kb deletion was subsequently identified within STX16 , the gene encoding syntaxin 16, which is now known to be the most frequent molecular cause of AD‐PHP1B. ( 12,25,26 )…”
Section: Introductionmentioning
confidence: 99%
“…Instead, genetic linkage studies revealed that the autosomal dominant variant of PHP1B (AD-PHP1B) is an imprinted disorder that is caused by a maternally inherited mutation centromeric of GNAS (20,21), which is furthermore associated with epigenetic changes at this locus (22). A 3kb deletion was subsequently identified within STX16, the gene encoding syntaxin 16, which is now known to be the most frequent molecular cause of AD-PHP1B (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%